2016
DOI: 10.1155/2016/6404197
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture Points Stimulation for Meniere’s Disease/Syndrome: A Promising Therapeutic Approach

Abstract: Objective. This study aims to explore evidence for acupuncture points stimulation (APS) in treatment of Meniere's disease (MD). Method. A literature search was conducted in seven databases including EMBASE, Medline, Cochrane Library, Web of Science, CBM, CNKI, and WangFang database and the data analysis was performed by using the RevMan version 5.3. Results. 12 RCTs with 993 participants were acquired after the search. The quality of most eligible studies was very low which limited the value of the meta-analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…The most recent found that acupuncture might be a promising therapeutic approach for MD, with some positive findings in vertigo control (negative for effect in hearing improvement and DHI), but currently available evidence is insufficient to make a definitive conclusion, with studies of poor quality. 225 An earlier review included Chinese language articles, finding studies of varying quality but an overall weight of evidence suggesting that there may be beneficial effects from acupuncture for those who are in an acute phase or who have had MD for years. 226 In addition, 1 RCT was found that compared Diaoshi Jifa acupressure with Ginkgo and oral betahistine and a control group that took only Ginkgo and oral betahistine.…”
Section: Acupuncture and Alternative Therapymentioning
confidence: 99%
“…The most recent found that acupuncture might be a promising therapeutic approach for MD, with some positive findings in vertigo control (negative for effect in hearing improvement and DHI), but currently available evidence is insufficient to make a definitive conclusion, with studies of poor quality. 225 An earlier review included Chinese language articles, finding studies of varying quality but an overall weight of evidence suggesting that there may be beneficial effects from acupuncture for those who are in an acute phase or who have had MD for years. 226 In addition, 1 RCT was found that compared Diaoshi Jifa acupressure with Ginkgo and oral betahistine and a control group that took only Ginkgo and oral betahistine.…”
Section: Acupuncture and Alternative Therapymentioning
confidence: 99%
“…Thus, it is critical to seek an effective and safe non-pharmacological therapy for VM prophylaxis, which can improve the quality of life of VM patients and reduce the side effects of pharmacotherapies and medical expense. On one hand, increasing the trials has favored the therapeutic effect of acupuncture for treating the major symptoms [i.e., vertigo/dizziness (13,25) and migraine (14,15)] and common comorbidities [e.g., anxiety (16) and depression (17)] of VM. On the other hand, although the pathogenesis of VM remains inconclusive, it is not only related to the central system but also a kind of recurrent peripheral vestibular disorders (9,38).…”
Section: Discussionmentioning
confidence: 99%
“…Given that the acupoint selection has a close correlation with the efficacy maximization of acupuncture, the acupoint prescription of our study is carefully schemed. The rationales for the acupoint prescription are mainly based on consensus with experienced acupuncture experts, which are highly overlapping with those adopted in previously published trials involving acupuncture for treating migraine (15), vertigo/dizziness (13), and emotional disorders (16,17). The acupoint selection in our study targets at alleviating major symptoms (i.e., migraine and vertigo/dizziness) and common comorbidities (i.e., emotional disorders) in VM patients, given that VM affects both the central and peripheral parts of the nervous system and previous studies revealed that Du meridian plays a vital role in treating various nervous system diseases (39,40), including vertigo and headache.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations